Homozygous variant rs2076530 of BTNL2 and familial sarcoidosis - Coudurier, M.; Freymond, N.; Aissaoui, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Rationale: Despite extensive studies, the pathogenesis of sarcoidosis is largely unknown. Although multiple environmental and putative infectious agents have been proposed, none was retained as a major contributor to the disease occurrence. Genetic predisposition to sarcoidosis was considered as a significant factor and numerous candidate genes have been reviewed. This last point was reinforced since the discovery of a pathogenic polymorphism (rs2076530 or G >A) of the BTNL2 gene, leading to an early truncation of the protein, which increases the relative risk of the disease. BTNL2 is known to act as a co-stimulatory molecule, inducing a negative signal to T-lymphocyte activation and the mutated gene is responsible for a truncated protein and disruption of membrane localization. Objectives: Our work attempted to confirm this observation in a highly penetrant familial form of sarcoidosis. Results: In this family, the disease was diagnosed in 5 members through 3 generations. Despite individual clinical specificities, all displayed severe forms of the disease. Peripheral blood samples were collected from 3 patients and 2 additional healthy children of the fourth generation. Analysis of the BTNL2 gene confirmed the presence of the pathogenic variant of BTNL2 on both alleles (A/A homozygous genotype) in all subjects tested. Conclusions: Our data suggest that the absence of a membrane anchored BTNL2 protein may increase genetic susceptibility to sarcoidosis and familial occurrence of the disease. This observation assessed the putative pathogenic involvement of the rs2076530 variant of BTNL2 in the development of this granulomatosis disease.